Propositions in the making experiments in a Whiteheadian laboratory - Faber, Roland, 1960-; Halewood, Michael; Davis, Andrew, 1987- (Contemporary Whitehead studies., 2020)
"Rather than a "logical assertion," Whitehead described a proposition as a "lure for feeling" for a collectivity to come. The unique contributions in Propositions in the Making articulate the newest reaches of Whiteheadian propositions for a postmodern world"--